Predicting Range Shifts of Five Alnus (Betulaceae) Species in China Under Future Climate Scenarios - Wenjie Yang; Zhilong Huang; Chenlong Fu; Zhuang Zhao; Xiaoyue Yang; Quanjun Hu; Zefu Wang (Plants)
Climate change poses significant challenges to forest biodiversity by altering species distributions. This study employed the MaxEnt model to predict the current and potential future suitable habitats of five Alnus species in China under four Shared Socioeconomic Pathways. Model accuracy was high, with temperature seasonality identified as the most influential variable. In addition, predicted range shifts showed species-specific patterns, with most species expanding toward higher latitudes and elevations. In contrast, Alnus ferdinandi-coburgii exhibited consistent habitat contraction. These findings enhance understanding of the climatic responses of Alnus species and provide a scientific basis for targeted conservation and management strategies under future climate change, and may offer insights into habitat responses of Alnus species in other temperate regions.